Maintenance of Peace and Development of Host Communities through Corporative Social Responsibility a Study of MTN in Onitsha South LGA of Anambra State - Jude Chidi Onyenama; Joseph Bamidele; Irefin Peace Oluwatoyin (International Journal of Advance Social Sciences and Education (IJASSE), 2023)
This Paper is concerned with the maintenance of peace and development of host communities through corporative social responsibility a study of MTN in Onitsha South L.G.A of Anambra State. Specific objectives investigated includes: The existence of corporate social responsibility in Onitsha South, whether MTN has corporate social responsibility programme in Onitsha South, the level of impact MTN corporate social responsibility programme has on the development and peace building in of Onitsha South, whether MTN corporate social responsibility programme contributes to maintenance of peace in Onitsha. This lead to formation of three research questions, are there existences of corporate social responsibility in Onitsha South? Does MTN have corporate social responsibility programme for development of Onitsha South? To what extent has MTN corporate social responsibility programme impacted on the development and peace building in Onitsha South? Is there any significant relationship between MTN corporate social responsibility programme and maintenance of peace in Onitsha South? The conceptual review, theoretical review and empirical review were used to through more lights on the research. The research employed a descriptive survey design to answer the three research questions. A questionnaire was designed and administered to the sample size of 399 subjects to find answers to the research questions. From the 399 copies of questionnaire distributed to the 399 respondents, 395 copies were returned while 4 copies were not returned. Therefore, a total of 395 questionnaire representing 98,99% of the respondents were used for the finally analysis below